2017
DOI: 10.1103/physrevb.95.235424
|View full text |Cite
|
Sign up to set email alerts
|

Weiss oscillations and particle-hole symmetry at the half-filled Landau level

Abstract: Particle-hole symmetry in the lowest Landau level of the two-dimensional electron gas requires the electrical Hall conductivity to equal ±e 2 /2h at half-filling. We study the consequences of weakly broken particle-hole symmetry for magnetoresistance oscillations about half-filling in the presence of an applied periodic one-dimensional electrostatic potential using the Dirac composite fermion theory proposed by Son. At fixed electron density, the oscillation minima are asymmetrically biased towards higher magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…(Mean-field theory means that fluctuations of an emergent gauge field coupling to the composite fermion are ignored.) Furthermore, both composite fermion theories yield identical predictions for a number of observables in mean-field theory [14,16,[19][20][21], e.g., thermopower at half-filling and magnetoroton spectra away from half-filling. These results suggest that the HLR and Dirac composite fermion theories may belong to the same universality class.…”
Section: 1 Motivationmentioning
confidence: 87%
See 3 more Smart Citations
“…(Mean-field theory means that fluctuations of an emergent gauge field coupling to the composite fermion are ignored.) Furthermore, both composite fermion theories yield identical predictions for a number of observables in mean-field theory [14,16,[19][20][21], e.g., thermopower at half-filling and magnetoroton spectra away from half-filling. These results suggest that the HLR and Dirac composite fermion theories may belong to the same universality class.…”
Section: 1 Motivationmentioning
confidence: 87%
“…However, the magnitude of the scalar potential is suppressed relative to the vector potential by a factor of B /d ≈ 1/50 [13]. Cheung et al [20] found that upon including the effects of the scalar potential in HLR mean-field theory, there is a slight correction to the expected locations of the oscillation minima both above and below ν = 1/2. The nature of the corrections are such that HLR mean-field theories of composite electrons or composite holes that take either k F = √ 4πn e or k F = 4π( B 2π − n e ) produce identical results.…”
Section: Weiss Oscillations and The ν = 1/2 Statementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1(c) zooms in around ν = 1/4. From the period of the modulation, a = 240 nm, we determine the expected positions for the primary i = 1 GR resistance minima according to [3,10,15,16,21,22,26,27]. The difference between the expected B i=1 for the two assumptions is very small and cannot be resolved in our experiments.…”
mentioning
confidence: 98%